Interrogating the Autonomy of the Nigerian State in Managing Farmer-Herder Conflict: Perspectives on Cases in Katsina State - Shaapera, Simon Aondohemba; Mohammed, Mohammed Haruna (Kashere Journal of Politics and International Relations, 2025)
This paper employs classical Marxist theory of the State to interrogate the autonomy of the Nigerian State in the management of farmer-herder conflicts in the country with particular reference to the cases in Katsina state between 2016 and 2021. The paper adopts survey research method of an ex post facto type to elicit data from respondents using structured questionnaire, unstructured oral interviews and focus group discussions (FGDs) as research instruments which were complemented by a review of extant body of literature. The major findings of the study revealed that in such a society where there are both the poor and the rich such as in the case of crop farmers and cattle herders in Nigeria, the State is expected to function, among other things, to maintain cohesion among the groups by ensuring the safety, security and well fare of all, and at the same time maintain its domination to manage the mode of production to reinforce class consciousness and struggles. However, in Nigeria, the post-colonial State enjoys not merely the relative autonomy that the State under developed capitalism has, but rather, has a distinct relative autonomy by virtue of its direct and obvious role in the economy, security and production, and that the State is able to dispense with the usual mediatory role of policies expected to provide for peace, security of lives and property. The State in the under-developed social formation is invariably characterized by weak and dependent economy as well as other features unique to its insecurity and under-developed institutions.